A simple spring has length $l$ and force constant $k$. It is cut into two springs of length ${l_1}$ and ${l_2}$ such that ${l_1} = n{l_2}$( n is an integer) the force constant of a spring of length ${l_1}$ is
A. $k(1 + n)$
B. $\dfrac{{nk}}{{n + 1}}$
C. $\dfrac{{\left( {1 + n} \right)k}}{n}$
D. $k$
Answer
Verified
122.7k+ views
Hint: We know that the length of the spring and force constant are inversely related. Total length $l$ of the spring is given as a sum of lengths ${l_1}$ and ${l_2}$. By substituting for each length in terms of respective force constants and on solving we can find the value of the spring constant of length ${l_1}$ in terms of the total spring constant $k$.
Complete step by step answer:
It is given that a spring has a length of $l$ .
The force constant of the spring is $k$.
Then the spring is cut into two springs of length ${l_1}$ and ${l_2}$ .
Relationship between ${l_1}$ and ${l_2}$ is given as
${l_1} = n{l_2}$
Where, n is an integer.
We need to find the force constant of the spring of length ${l_1}$ .
We know that the length of a spring and force constant are inversely related.
So, we can write it as
$l \propto \dfrac{1}{k}$
$ \Rightarrow l = \dfrac{c}{k}$ (1)
Where, c is a constant of proportionality.
Let ${k_1}$ be the force constant of spring with length ${l_1}$ and ${k_2}$ be the force constant of spring with length ${l_2}$.
Then we can write
$ \Rightarrow {l_1} = \dfrac{c}{{{k_1}}}$ (2)
And
$ \Rightarrow {l_2} = \dfrac{c}{{{k_2}}}$ (3)
We know that the total length $l$ is the sum of ${l_1}$ and ${l_2}$ .
$ \Rightarrow l = {l_1} + {l_2}$
$ \Rightarrow l = {l_1} + \dfrac{{{l_1}}}{n}$
$\because {l_1} = n{l_2}$
Substituting the value of $l$ and ${l_1}$from equation 1 and 2, we get
$ \Rightarrow \dfrac{c}{k} = \dfrac{c}{{{k_1}}} + \dfrac{c}{{n{k_1}}}$
Now let us solve for ${k_1}$ .
$ \Rightarrow \dfrac{1}{k} = \dfrac{1}{{{k_1}}} + \dfrac{1}{{n{k_1}}}$
$ \Rightarrow \dfrac{1}{k} = \dfrac{{n + 1}}{{n{k_1}}}$
$ \Rightarrow {k_1} = \dfrac{{n + 1}}{n}k$
This is the value of the spring constant of length ${l_1}$ .
Hence, the correct answer is option C.
Note: Remember that the length and spring constant are inversely related. If we increase the length of the spring then the force constant will decrease and if you decrease the length of spring then the force constant will increase. So, if we cut a spring in half the spring constant of each half will be doubled. In our case since ${l_1} = n{l_2}$ The relation between spring constants of these parts will then be ${k_2} = n{k_1}$
Complete step by step answer:
It is given that a spring has a length of $l$ .
The force constant of the spring is $k$.
Then the spring is cut into two springs of length ${l_1}$ and ${l_2}$ .
Relationship between ${l_1}$ and ${l_2}$ is given as
${l_1} = n{l_2}$
Where, n is an integer.
We need to find the force constant of the spring of length ${l_1}$ .
We know that the length of a spring and force constant are inversely related.
So, we can write it as
$l \propto \dfrac{1}{k}$
$ \Rightarrow l = \dfrac{c}{k}$ (1)
Where, c is a constant of proportionality.
Let ${k_1}$ be the force constant of spring with length ${l_1}$ and ${k_2}$ be the force constant of spring with length ${l_2}$.
Then we can write
$ \Rightarrow {l_1} = \dfrac{c}{{{k_1}}}$ (2)
And
$ \Rightarrow {l_2} = \dfrac{c}{{{k_2}}}$ (3)
We know that the total length $l$ is the sum of ${l_1}$ and ${l_2}$ .
$ \Rightarrow l = {l_1} + {l_2}$
$ \Rightarrow l = {l_1} + \dfrac{{{l_1}}}{n}$
$\because {l_1} = n{l_2}$
Substituting the value of $l$ and ${l_1}$from equation 1 and 2, we get
$ \Rightarrow \dfrac{c}{k} = \dfrac{c}{{{k_1}}} + \dfrac{c}{{n{k_1}}}$
Now let us solve for ${k_1}$ .
$ \Rightarrow \dfrac{1}{k} = \dfrac{1}{{{k_1}}} + \dfrac{1}{{n{k_1}}}$
$ \Rightarrow \dfrac{1}{k} = \dfrac{{n + 1}}{{n{k_1}}}$
$ \Rightarrow {k_1} = \dfrac{{n + 1}}{n}k$
This is the value of the spring constant of length ${l_1}$ .
Hence, the correct answer is option C.
Note: Remember that the length and spring constant are inversely related. If we increase the length of the spring then the force constant will decrease and if you decrease the length of spring then the force constant will increase. So, if we cut a spring in half the spring constant of each half will be doubled. In our case since ${l_1} = n{l_2}$ The relation between spring constants of these parts will then be ${k_2} = n{k_1}$
Recently Updated Pages
The ratio of the diameters of two metallic rods of class 11 physics JEE_Main
What is the difference between Conduction and conv class 11 physics JEE_Main
Mark the correct statements about the friction between class 11 physics JEE_Main
Find the acceleration of the wedge towards the right class 11 physics JEE_Main
A standing wave is formed by the superposition of two class 11 physics JEE_Main
Derive an expression for work done by the gas in an class 11 physics JEE_Main
Trending doubts
JEE Main 2025 Session 2: Application Form (Out), Exam Dates (Released), Eligibility & More
JEE Main Login 2045: Step-by-Step Instructions and Details
Class 11 JEE Main Physics Mock Test 2025
JEE Main Chemistry Question Paper with Answer Keys and Solutions
JEE Main Exam Marking Scheme: Detailed Breakdown of Marks and Negative Marking
JEE Main 2023 January 24 Shift 2 Question Paper with Answer Keys & Solutions
Other Pages
JEE Advanced Marks vs Ranks 2025: Understanding Category-wise Qualifying Marks and Previous Year Cut-offs
NCERT Solutions for Class 11 Physics Chapter 1 Units and Measurements
NCERT Solutions for Class 11 Physics Chapter 9 Mechanical Properties of Fluids
Units and Measurements Class 11 Notes: CBSE Physics Chapter 1
JEE Advanced 2025: Dates, Registration, Syllabus, Eligibility Criteria and More
NCERT Solutions for Class 11 Physics Chapter 2 Motion In A Straight Line